2010
DOI: 10.1155/2010/890674
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Endosomal Sorting Complex Required for Transport inEntamoeba histolyticaand Characterization of the EhVps4 Protein

Abstract: Eukaryotic endocytosis involves multivesicular bodies formation, which is driven by endosomal sorting complexes required for transport (ESCRT). Here, we showed the presence and expression of homologous ESCRT genes in Entamoeba histolytica. We cloned and expressed the Ehvps4 gene, an ESCRT member, to obtain the recombinant EhVps4 and generate specific antibodies, which immunodetected EhVps4 in cytoplasm of trophozoites. Bioinformatics and biochemical studies evidenced that rEhVps4 is an ATPase, whose activity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 54 publications
1
45
0
1
Order By: Relevance
“…In E. histolytica, we found a highly conserved ESCRT machinery with 19 putative components representing all complexes. These findings have been experimentally confirmed by determining the expression of most ESCRT gene transcripts (López-Reyes, et al, 2010). Furthermore, our current in silico results suggest that some E. histolytica ESCRT-0 to -III components contain putative FYVE or ubiquitin binding domains, both important to recruit cargo molecules to endosomal membranes.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In E. histolytica, we found a highly conserved ESCRT machinery with 19 putative components representing all complexes. These findings have been experimentally confirmed by determining the expression of most ESCRT gene transcripts (López-Reyes, et al, 2010). Furthermore, our current in silico results suggest that some E. histolytica ESCRT-0 to -III components contain putative FYVE or ubiquitin binding domains, both important to recruit cargo molecules to endosomal membranes.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, this protein is located at MVB-like structures in E. histolytica trophozoites and is structurally related to Bro1 (Bañuelos et al, 2005), an accessory protein that interacts with the ESCRT-III complex in yeast. Recently, our research group reported the presence of a set of 19 putative ESCRT proteins in this parasite and characterized a yeast Vps4 homologue by analyzing its ATPase function and relationship to parasite virulence in wild type and mutant cells (López-Reyes et al, 2010). Results derived from these studies strongly suggest that E. histolytica possesses a well conserved ESCRT machinery.…”
Section: Endocytosis and The Mvb Pathway In Parasitic Protozoamentioning
confidence: 99%
See 1 more Smart Citation
“…We then focused on Alix (EHI_167710), which has two homologues (sharing the BRO domain) previously described in E. histolytica : the ADH112 adhesin (EHI_181220) (Lopez‐Reyes et al ., ) and a second protein sharing domain similarities (EHI_165220), (Perdomo et al ., ). We detected Alix with an antibody specifically recognizing EHI_167710, a confirmed protein present in isolated amoebic vesicles and involved in endosomal trafficking (Perdomo et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…An ATPase assay confirmed Vps4 ATPase activity, and overexpression of an enzymatically dead mutant impairs phagocytosis and the organism’s ability to cause hepatic abscesses in hamsters [100]. Three E. histolytica proteins contain a Bro1 domain, and thus may be homologues of Bro1/Vps31: ADH112, ADH112-like 1 and ADH112-like 2.…”
Section: Functional Homology In Trafficking Machinery Between Divermentioning
confidence: 99%